Assessment of rotatory laxity in anterior cruciate ligament-deficient knees using magnetic resonance imaging with Porto-knee testing device - Mendes, João Espregueira (2012)
Purpose Objective evaluation of both antero-posterior translation and rotatory laxity of the knee remains a target to be accomplished. This is true for both preoperative planning and postoperative assessment of different ACL reconstruction emerging techniques. The ideal measurement tool should be simple, accurate and reproducible, while enabling to assess both ‘‘anatomy’’ and ‘‘function’’ during the same examination. The purpose of this study is to evaluate the clinical effectiveness of a new in-housedeveloped testing device, the so-called Porto-knee testing device (PKTD). The PKTD is aimed to be used on the evaluation of both antero-posterior and rotatory laxity of the knee during MRI exams. Methods Between 2008 and 2010, 33 patients with ACLdeﬁcient knees were enrolled for the purpose of this study. All patients were evaluated in the ofﬁce and under anesthesia with Lachman test, lateral pivot-shift test and anterior drawer test. All cases were studied preoperatively with KT-1000 and MRI with PKTD, and examinations performed by independent observers blinded for clinical evaluation. During MRI, we have used a PKTD that applies antero-posterior translation and permits free tibial rotation through a standardized pressure (46.7 kPa) in the proximal posterior region of the leg. Measurements were taken for both knees and comparing side-to-side. Five patients with partial ruptures were excluded from the group of 33. Results For the 28 remaining patients, 3 women and 25 men, with mean age of 33.4 ± 9.4 years, 13 left and 15 right knees were tested. No signiﬁcant correlation was noticed for Lachman test and PKTD results (n.s.). Pivot-shift had a strong positive correlation with the difference in anterior translation registered in lateral and medial tibia plateaus of injured knees (cor. coefﬁcient = 0.80; p\0.05), and with the difference in this parameter as compared to side-to-side (cor. coefﬁcient = 0.83; p\0.05). Considering the KT-1000 difference between injured and healthy knees, a very strong positive correlation was found for side-to-side difference in medial (cor. coefﬁ- cient = 0.73; p\0.05) and lateral (cor. coefﬁcient = 0.5; p\0.05) tibial plateau displacement using PKTD. Conclusion The PKTD proved to be a reliable tool in assessment of antero-posterior translation (comparing with KT-1000) and rotatory laxity (compared with lateral pivotshift under anesthesia) of the ACL-deﬁcient knee during MRI examination